Holiday house : a series of tales - Sinclair, Catherine, 1800-1864 (Preservation and Access for American and British Children's Literature, 1850-1869 (NEH PA-23536-00), 1853)
"In these pages the author has endeavored to paint that species of noisy, frolicsome, mischievous children, which is now almost extinct ... and when, admidst many faults and eccentricities, there is still some individuality of character and feeling allowed to remain."--Preface, p.v.